1991
DOI: 10.1080/01652176.1991.9694309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a deficient magnesium supply during the dry period on bone turnover of dairy cows at parturition

Abstract: SUMMARY. The bone activity and bone mineral content in rib bones resected from 33 dairy cows between 3 and 8 h after parturition were measured, and the effects upon them of a deficient supply of dietary magnesium (Mg) during the last seven weeks of pregnancy were studied. The cows were fed a diet containing either 0.22% magnesium (low Mg) or 0.82% magnesium (high Mg) in the dry matter (DM), and the potassium content of both rations was increased to approximately 4.1% in the DM to reduce the absorption of magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…The Mg concentration was lower in primiparous cows than in older cows, but the reason for this is not clear. In contrast, van Mosel et al (1991) previously showed that lowparity cows fed a low-Mg diet had a higher concentration of Mg in plasma than did high-parity cows.…”
Section: Discussionmentioning
confidence: 87%
“…The Mg concentration was lower in primiparous cows than in older cows, but the reason for this is not clear. In contrast, van Mosel et al (1991) previously showed that lowparity cows fed a low-Mg diet had a higher concentration of Mg in plasma than did high-parity cows.…”
Section: Discussionmentioning
confidence: 87%
“…We took the samples for mineral balance studies during a short period. Most cows are rapidly in negative Ca balance during the early days of lactation [27]. In addition, the contents of intestine are stable after about 7 days from alteration of diet.…”
Section: Discussionmentioning
confidence: 96%
“…The tissue sheets, after washed fully with physiological saline solution, were attached on the Ussing chamber (exposed area 1 cm 2 ) to measure the 27 T. Kozakai et al…”
Section: In Vitro Ca Absorption In Tissue Sheets Of the Gastrointestimentioning
confidence: 99%
“…A redução nos valores da concentração de cálcio no dia do parto foi similar às observações feitas por alguns autores que verificaram redução do mineral com a aproximação do parto e no dia do parto (Blum et al 1972, Wilson et al 1977, Van Mosel & Corlett 1990, Van Mosel et al 1991, Vanden Top et al 1995, Goff & Horst 1997a, Souza Júnior et al 2011, Buture 2009.…”
Section: Quadro 4 Valores De Condição Corporal Das Vacas Mestiças Plunclassified